The effects of training female students in emotion regulation techniques on their social problem-solving skills and social anxiety: a randomized controlled trial - Ashraf Akbari; Camellia Torabizadeh; Narjes Nick; Giti Setoodeh; Parvin Ghaemmaghami (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Social anxiety is one of the most prevalent anxiety-related disorders among adolescents with many adverse effects on the social and academic lives of this population. In addition, poor social problem-solving skills can aggravate anxiety in individuals suffering from anxiety. Emotion regulation can help adolescents control and moderate their feelings, thereby enabling them to understand their emotions better, cope with their negative emotions in a positive way, and adopt a more realistic approach to solving their problems. The objective of the present study is to investigate the effects of educating female students in emotion regulation techniques on their social problem-solving skills and social anxiety. Method This study was a randomized controlled trial conducted in Iran, utilizing a pretest-posttest design with control and intervention groups. The subjects were 47 female high-school second graders who were randomly divided into a control (25 students) and an intervention group (22 students). The intervention group was collectively educated in emotion regulation techniques in weekly one-hour sessions for eight weeks. The control group did not receive any intervention. The social anxiety and social problem-solving scales were completed by both groups before, immediately after, and one month after the intervention. The collected data were analyzed in SPSS v. 22 and level of significance was set at p < 0.05. Result Data analysis of the intervention group compared to the control group demonstrated that group training in emotional regulation techniques effectively increased social problem-solving skills scores (p = 0.003) and decreased social anxiety scores (p < 0.0001) among students in the intervention group compared to their pretest scores. These effects remained stable during the follow-up phase. Conclusion In view of the prevalence of social anxiety among adolescents, it is suggested that the policymakers and administrators in the education system promote emotion regulation skills in adolescent students to facilitate their psychological adaptation and improve their emotional capabilities. Trial registration The present study was registered under the code IRCT20220413054521N1 (Registration date: 27/02/2024) in the Iranian Registry of Clinical Trials.